Kinetic and kinematic changes during resisted sprinting due to towing three common parachute sizes - Gleadhill, S.; Nagahara, R. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Different sized parachutes may alter applied resistance during parachute towing (PT), changing results of resisted sprint training interventions. Thus, it was hypothesized that there may be significant net anteroposterior ground reaction force and impulse differences due to parachute size towed. METHODS: Fifteen male sprinters completed control and PT sprints over a 50 m force platform system. Estimated aerodynamic drag, ground reaction forces and kinematic differences during the maximum speed phase were compared between control (no parachute) and PT trials with small (0.39 m2), medium (0.54 m2) and large (0.72 m2) parachutes, using One-way ANOVA (significance set at P<0.050) with Tukey`s HSD post-hoc (critical Q value = 3.746) tests. RESULTS: No significant (P>0.050) step length, step frequency, propulsive mean force, vertical mean force, or vertical impulse differences between trials. There was a significant anteroposterior impulse difference (P<0.001, Q=4.574) between small and medium PT, but no differences between medium and large PT. Compared to the control trial, all PT trials increased anteroposterior net mean force (P<0.001), anteroposterior net impulse (P<0.001), and propulsive impulse (P<0.001). However, only PT with the large parachute significantly reduced running speed (P<0.050, Q=3.792), braking mean force (P<0.050, Q=4.130) and braking impulse (P<0.001, Q=5.987), compared to the control trial. CONCLUSIONS: A large parachute may be most effective for PT (compared to control trial) to overload the body during the maximum speed phase in a single session.